2015
DOI: 10.1016/j.aop.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Periodically driven ergodic and many-body localized quantum systems

Abstract: We study dynamics of isolated quantum many-body systems whose Hamiltonian is switched between two different operators periodically in time. The eigenvalue problem of the associated Floquet operator maps onto an effective hopping problem. Using the effective model, we establish conditions on the spectral properties of the two Hamiltonians for the system to localize in energy space.We find that ergodic systems always delocalize in energy space and heat up to infinite temperature, for both local and global drivin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
397
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(418 citation statements)
references
References 36 publications
11
397
1
1
Order By: Relevance
“…In the translation-invariant setting, Floquet eigenstates are short-range correlated and resemble infinite temperature states which cannot exhibit symmetry breaking [16,19,20]. Under certain conditions, however, prethermal time-crystal-like dynamics can persist for long times [21,22] even in the absence of localization before ultimately being destroyed by thermalization [18,23].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the translation-invariant setting, Floquet eigenstates are short-range correlated and resemble infinite temperature states which cannot exhibit symmetry breaking [16,19,20]. Under certain conditions, however, prethermal time-crystal-like dynamics can persist for long times [21,22] even in the absence of localization before ultimately being destroyed by thermalization [18,23].…”
mentioning
confidence: 99%
“…Subsequent work developed more precise definitions of such time translation symmetry breaking (TTSB) [6][7][8] and ultimately led to a proof of the "absence of (equilibrium) quantum time crystals" [9]. However, this proof leaves the door open to TTSB in an intrinsically out-of-equilibrium setting, and pioneering recent work [10,11] has demonstrated that quantum systems subject to periodic driving can indeed exhibit discrete TTSB [10-13]; such systems develop persistent macroscopic oscillations at an integer multiple of the driving period, manifesting in a sub-harmonic response for physical observables.An important constraint on symmetry breaking in many-body Floquet systems is the need for disorder and localization [10][11][12][13][14][15][16][17][18]. In the translation-invariant setting, Floquet eigenstates are short-range correlated and resemble infinite temperature states which cannot exhibit symmetry breaking [16,19,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An exciting possibility is to obtain a topologically nontrivial steady state for an interacting, periodically driven system [15][16][17]19,20]. The common wisdom dictates that a periodically driven system with dispersive modes is doomed to evolve into a highly random state that is essentially an infinite temperature state as far as any finite-order correlation functions are concerned [51,[59][60][61][62][63]. Our results on the single-particle level demonstrate that it is possible to obtain a topological Floquet spectrum with no delocalized states away from the edges of the system.…”
Section: Discussionmentioning
confidence: 99%
“…The robust subharmonic synchronization of the many-body Floquet system is the essence of the discrete time crystal phase [7][8][9][10] . In a DTC, the underlying Floquet drive should generally be accompanied by strong disorder, leading to manybody localization 13 and thereby preventing the quantum system from absorbing the drive energy and heating to infinite temperatures [14][15][16][17] .…”
mentioning
confidence: 99%